Fixing fractured nations : the challenge of ethnic separatism in the Asia-Pacific - Wirsing, Robert; Ahrari, Mohammed E. (New York : Palgrave Macmillan, 2010)
Asia's rising power and wealth offer its many oppressed ethnic minorities hope for greater political freedom and an end to violence. But the reality of this hope is cast in doubt by acute separatist conflict. This book provides fresh and factual assessments of separatist struggles and prospects for conflict resolution in nine countries of Asia --Provided by publisher.
Machine generated contents note: Introduction: Ethnic Separatism in Asia: What Lies Ahead?--R. Wirsing Part I: South East Asia Thailand: Southern Discomfort: Separatist Conflict in the Kingdom of Thailand--I. Storey Myanmar/Burma: Resolving the Burmese Imbroglio: A Multilateral Solution?--M. Malik Philippines: Manilas Mindanao Muddle--V. Watson Indonesia: Letting Go to Hold On--A. Smith Part II: South Asia Pakistan: Ethnic Separatism in Balochistan: Tribal Turbulence on the Energy Corridor--R. Wirsing India: Nation and the Spirals of Insecurity: How the State Responds to Ethnic Separatism in Indias Northeast--S.K. Das India &--Pakistan: Dangerous Place: Kashmiri Separatism in a Disputed Territory--R. Wirsing Sri Lanka: Managing Ethnic Conflict in Sri Lanka: Going Beyond LTTE--S.Akhtar Part III: East Asia China: Retribution &--Retaliation: Uyghur Separatism &--Chinese Security in Xinjiang--E.Davis China: Tibet: At the Crossroads of Ethnic Nationalism &--Geopolitical Realism--P.Smith Part IV: Pacific Islands Papua New Guinea: The Melting Pot: Ethnicity, Identity &--Separatism in Bougainville, Papua New Guinea--J.Rolfe Conclusion: Ethnic Separatism in Geopolitical Perspective--E.Ahrari.
Includes bibliographical references and index.
Keywords: Peace-building -- Asia; Conflict management -- Asia; Peace-building -- Pacific Area; Conflict management -- Pacific Area; Minorities -- Asia; Minorities -- Pacific Area; Asia -- Ethnic relations -- Political aspects; Pacific Area -- Ethnic relations -- Political aspects